Effects of water supplementation of an organic acid-trace mineral complex on production and slaughter parameters, intestinal histomorphology, and macronutrient digestibility in growing ostriches. (17th April 2019) - Seyfori, Hossein; Ghasemi, Hossein Ali; Hajkhodadadi, Iman; Hafizi, Maryam
ABSTRACT: An experiment was conducted to study the effect of water supplementation of organic acid-chelated trace minerals (OTM) on production traits, carcass characteristics, intestinal histomorphology, and nutrient digestibility in African ostrich chicks from 8 to 12 mo of age. A total of 20 growing ostriches, with almost similar body weight (73.4 to 75.8 kg), were individually distributed in outdoor paddocks of ≈ 24 m 2 and were randomly allocated into 1 of the following 4 treatments: (1) control/basal diet, (2) low OTM (basal diet + 100 mg/bird/day OTM powder in water), (3) medium OTM (basal diet + 1 g/bird/day OTM powder in water), and (4) high OTM (basal diet + 2 g/bird/day OTM powder in water). The body weight gain and feed conversion efficiency were greater ( P < 0.05) in ostriches receiving medium-OTM treatment compared to control during the overall phase of the experiment. Although whole carcass yield, the yield of parts, and the relative weights of internal organs were not affected by experimental treatments, supplementation of higher amounts of OTM (medium- and high-OTM) resulted in a decrease ( P < 0.05) in the subcutaneous and abdominal fat contents. Medium- and high-OTM treatments increased ( P < 0.05) the villus height/crypt depth ratio in the jejunum and ileum compared with control and low-OTM treatments. Moreover, ostriches receiving the medium-OTM had also higher total tract apparent digestibility of energy ( P = 0.048), ether extract ( P = 0.050), crude fiber ( P = 0.063), and higher AMEn ( P = 0.094) than the control group. Overall, supplementation of OTM at the level of 1 g/bird/day to the drinking water of growing ostriches fed diets containing the recommended levels of inorganic trace minerals could beneficially affect productive performance, nutrient digestibility, and intestinal morphology.